2003
DOI: 10.1586/14760584.2.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal adjuvants and anti-infection and anti-immunopathology vaccines based on cholera toxin, cholera toxin B subunit and CpG DNA

Abstract: The mucosal immune system consists of an integrated network of lymphoid cells that work in concert with innate host factors to promote host defence. Mucosal immunization can be used both to protect the mucosal surfaces against colonization and invasion by microbial pathogens and to provide a means for immunological treatment of selected autoimmune, allergic or infectious-immunopathological disorders through the induction of antigen-specific tolerance. The development of mucosal vaccines, whether for prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(102 citation statements)
references
References 20 publications
6
86
1
9
Order By: Relevance
“…To date, there are significant efforts and interest in the development of mucosal vaccines against various microbes and notable pioneering accomplishments using lactic acid bacteria as live vectors for oral delivery (21,36,37). Accordingly, one scientific consensus is that the next generation of vaccines should ideally be given orally in single doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, there are significant efforts and interest in the development of mucosal vaccines against various microbes and notable pioneering accomplishments using lactic acid bacteria as live vectors for oral delivery (21,36,37). Accordingly, one scientific consensus is that the next generation of vaccines should ideally be given orally in single doses.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that some recombinant lactic acid bacteria vaccine candidates induced elevated levels of antigen-specific secretory IgA (6), the predominant Ig class at mucosal surfaces (21). Moreover, one feature of this class of IgA is that it resists proteases rendering these antibodies critical for mucosal immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not significant, this delayed effect is well compatible to the innate cellular response which was measured in the ELISPOT assay and has already been described for CtxB or Salmonella alone. 15,46 Furthermore, also the PSA-secreting strain achieved significant protection at day 14, which indicates that also this strain induced a Tcell response which was below the detection threshold. In contrast, the strain separately expressing CtxB and PSA Figure 3 ELISPOT analysis of PPSA 18-specific cellular responses.…”
Section: Discussionmentioning
confidence: 94%
“…The native CtxB is one of the best studied and most effective experimental mucosal adjuvants known today. 15,16 In addition, this protein is a highly efficient carrier molecule for chemically or genetically conjugated antigens for eliciting mucosal and systemic antibody responses, as well as mucosal tolerance for prophylactic vaccines against autoimmune diseases. [17][18][19] To test the hypothesis that CtxB can enhance the antitumor efficacy of a cancer vaccine, several plasmids, encoding different combinations between PSA and CtxB, were generated.…”
Section: Introductionmentioning
confidence: 99%